Pengaruh Gaya Kepemimpinan dan Motivasi Kerja Terhadap Kinerja Karyawan pada PT. Makmur Jaya Pamekasan - Istianah Asas; Martha tona (Triwikrama: Jurnal Ilmu Sosial, 2023)
This study aims to determine the effect of leadership style and work motivation on the performance of employees at the PT. Makmur Jaya Pamekasan. Data obtained from distributing questionnaires to employees of PT. Makmur Jaya Pamekasan. This study uses data collection techniques, namely saturated sampling, where all members of the population used are all employees at PT. Makmur Jaya Pamekasan. Data analysis uses multiple linear regression to obtain a comprehensive picture of the relationship between variables. The results of the study show that leadership style and work motivation have a positive and significant effect on the performance of the employees PT. Makmur Jaya Pamekasan